2021
DOI: 10.1177/00400599211027299
|View full text |Cite
|
Sign up to set email alerts
|

You’re Hired!

Abstract: While job interviewing training is part of the transition planning and school-to-work curriculum, using virtual reality (VR) can be a valuable addition to the current curriculum, specifically given the unique characteristics of individuals with ASD. This article will provide step-by step procedures to integrate VR into the current classroom transition training program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Notably, the field has begun to evaluate the efficacy and initial effectiveness of VR-JIT among transition-age youth with disabilities. Specifically, one pilot study found that VR-JIT was associated with improved skills and interview self-efficacy primarily among transition-age youth with autism in a lab-based study (Smith, Ginger, Wright, Wright, Taylor, et al, 2014); results which were then independently replicated in community settings (Arter et al, 2018; Genova et al, 2021; Ward & Esposito, 2019). However, only the original pilot evaluated whether VR-JIT engagement was associated with vocational outcomes, which revealed that VR-JIT trainees, as compared with a control group, were more likely to get a job or volunteer position within 6 months (Smith, Fleming, Wright, Losh, et al, 2015).…”
mentioning
confidence: 99%
“…Notably, the field has begun to evaluate the efficacy and initial effectiveness of VR-JIT among transition-age youth with disabilities. Specifically, one pilot study found that VR-JIT was associated with improved skills and interview self-efficacy primarily among transition-age youth with autism in a lab-based study (Smith, Ginger, Wright, Wright, Taylor, et al, 2014); results which were then independently replicated in community settings (Arter et al, 2018; Genova et al, 2021; Ward & Esposito, 2019). However, only the original pilot evaluated whether VR-JIT engagement was associated with vocational outcomes, which revealed that VR-JIT trainees, as compared with a control group, were more likely to get a job or volunteer position within 6 months (Smith, Fleming, Wright, Losh, et al, 2015).…”
mentioning
confidence: 99%